The association of T786C and G894T polymorphisms of eNOS gene with diabetic retinopathy in Greece. Issue 5 (September 2022) - Gouliopoulos, Nikolaos; Siasos, Gerasimos; Oikonomou, Dimitra; Oikonomou, Evangelos; Konsola, Theodosia; Kollia, Christina; Athanasiou, Dimitris; Dimitropoulos, Stathis; Rouvas, Alexandros; Kassi, Eva; Tousoulis, Dimitrios; Moschos, Marilita M.
Purpose: To investigate whether eNOS T786C (rs2070744) and G894T (rs1799983) gene polymorphisms are associated with diabetic retinopathy in Greek diabetic patients. Materials: 271 patients with type-2 diabetes mellitus participated in our study; 130 suffered from diabetic retinopathy and 141 not. All the patients underwent a complete ophthalmological examination, while clinical and demographic data were assessed. Furthermore, they were genotyped for rs2070744 and rs1799983 single nucleotide polymorphisms of eNOS gene. Results: Regarding the clinical and demographic data, no significant differences were detected between the studied groups, except for hemoglobin A1c levels and the frequency of insulin treatment (higher in patients with diabetic retinopathy). The frequency of rs1799983 GT genotype was significantly elevated in patients with diabetic retinopathy (55% vs. 40%, P  = 0.011) and was associated with a 2-fold increased risk of developing retinopathy (OR 1.92, 95% CI 1.16–3.17). Furthermore, we demonstrated that the aforementioned genotype was significantly and independently associated with increased odds for retinopathy onset in diabetic subjects (OR 2.23, 95% CI 1.28–3.90, P  = 0.005), regardless of the impact of other confounders. Conclusions: We documented that rs1799983 GT genotype could be recognized as an independent risk factor of retinopathy in Greek patients with type-2 diabetes mellitus, while no role for rs2070744 polymorphism was identified. Further research in different ethnic groups will clarify the exact association of these polymorphisms with the risk for diabetic retinopathy development.